Evaluation of Measurement Tools for Tobacco Product Displays: Is there an App for that? - Todd B. Combs; Sarah Moreland-Russell; Jason Roche (AIMS Press, 2015)
Tobacco product displays are a pervasive presence in convenience stores, supermarkets, pharmacies, and other retailers nationwide. The influence that tobacco product displays have on purchases and tobacco product initiation, particularly on young people and other vulnerable populations, is well known. An objective measurement tool that is valid, reliable, and feasible to use is needed to assess product displays in the retail setting. This study reports on the relative accuracy of various tools that measure area and/or distance in photos and thus could be applied to product displays. We compare results of repeated trials using five tools. Three tools are smartphone apps that measure objects in photos taken on the device; these are narrowed down from a list of 284 candidate apps. Another tool uses photos taken with any device and calculates relative area via a built-in function in the Microsoft Office Suite. The fifth uses photos taken with the Narrative Clip, a "life-logging" wearable camera. To evaluate validity and reliability, we assess each instrument's measurements and calculate intra-class correlation coefficients. Mean differences between observed measurements (via tape measure) and those from the five tools range from just over one square foot to just over two square feet. Most instruments produce reliable estimates though some are sensitive to the size of the display. Results of this study indicate need for future research to test innovative measurement tools. This paper also solicits further discussion on how best to transform anecdotal knowledge of product displays as targeted and disproportionate marketing tactics into a scientific evidence base for public policy change.